(3JgPjH GdCUhd Edi Yde GdCUhds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3ESeGYjd Hf eMeO Ydj GdTjQhGfjs)
(3ChdgG (B:s
(3GdMeO ddg QGaY OQLGJ GdYGQajf(B... (3CeG HYO agPG cJGH JgPjH GdCUhd(B...s
(3BNQgG (B:s
(3aj GdWQjb hCeG aj GdCUd hGdaQY eYG hgh SDGd GdaQb, hdjcf gPG BNQ eG fPcQg aj gPG GdcJGH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs